SISTEM INFORMASI BIMBINGAN KONSELING DI SMKN 1 CIRUAS KABUPATEN SERANG - Widyawati Widyawati; Yul Hendra; Nuni Khairunnisa (Jurnal Ilmiah Sains dan Teknologi, 2021)
The counseling at SMKN I Ciruas is a process of service to parents of students to control the deveIopment and activities of students in school. Along with the development of information technology, guidance and counseling services can also take advantage of existing media or information technology so that it can facilitate parental supervision of their children. Data collection techniques are carried out by interviewing, observing, reviewing documents and archives. To describe how this counseling guidance information system works, the Data Flow Diagram (DFD) method is used which is website-basead’ using the PHP programming language and the database used MySQL. The purpose of this system is designed to facilitate the process of student data collection, processing student data, archiving student data, and facilitate parental control of the behaviour and behaviour of each child in the school and provide information to the school about student counseling data. The proposed system is a computerized and online counseling guidance system so that parents can find out about violations that have been committed by their children at school